EFEKTIVITAS STRATEGI BRANDING DALAM PENGGUNAAN APLIKASI NEW PASAR.ID OLEH NASABAH BANK RAKYAT INDONESIA UNIT TANJUNG - Afifah, Yulia; Siswanto, Adil (Jurnal Manajemen dan Profesional, 2025)
This study examines the effectiveness of branding strategies in encouraging the use of the New Pasar.id application by BRI Unit Tanjung customers. The background is the low adoption rate of this application in Tanjung Jember Market despite promotions, raising questions about the success of the implemented branding strategy. The purpose of this study is to determine how customers use the application, analyze the branding strategy of BRI Unit Tanjung, and assess its effectiveness. The method used is a descriptive qualitative approach with observation techniques, semi-structured interviews, and documentation of internal BRI parties and customer users of the application. The results show that the branding strategy includes brand positioning, brand identity, brand personality, and brand communication. However, its effectiveness is still low due to obstacles to understanding, limited access to information, and a lack of continuous promotion. In conclusion, BRI's branding strategy is not optimal in increasing application usage. A more educational, massive, and consistent branding approach is needed. The originality of this study lies in its focus on the adoption of digital applications in traditional markets through an analysis of branding strategies in the local banking sector